The Bitcoin yield gap in Colombia: unraveling the influence of FX and Bitcoin convenience yields - Jairo Andrés Rendón (Humanities & Social Sciences Communications)
Abstract This study examines why Bitcoin consistently traded at a discount in Colombia compared to the US market between April 2020 and July 2023. We introduced the “Bitcoin yield gap,” representing the difference between Bitcoin’s trading price in Colombia and its global price. Using robust ordinary least squares regression, we found a positive relationship between foreign exchange (FX) convenience yields and the yield gap, while Bitcoin convenience yields did not show a significant relationship. Additionally, Bitcoin network demand was significantly associated with the yield gap without affecting other regression parameters. These findings highlight that the yield gap is predominantly driven by dynamics in the domestic FX market, illustrating the interplay between traditional FX markets and the digital cryptocurrency landscape in Colombia.